Toward a Molecular Understanding of Adaptive Immunity: A Chronology, Part III - Smith, Kendall A. (Frontiers in Immunology, 2014)
Early reports on TCR signaling uncovered a rapid increase in intracellular calcium concentration and the activation of calcium-dependent protein kinase as necessary for T cell activation. Cytolytic T cell clones were instrumental in the discovery of intracellular cytolytic granules, and the isolation of the perforin and granzyme molecules as the molecular effectors of cell-mediated lysis of target cells via apoptosis. Cytolytic T cell clones and TCR cDNA clones were also instrumental for the generation of TCR transgenic animals, which provided definitive evidence for negative selection of self-reactive immature thymocytes. In addition, studies of TCR complex signaling of immature thymocytes compared with mature T cells were consistent with the interpretation that negative selection occurs as a consequence of the incapacity of immature cells to produce IL-2, resulting in cytokine deprivation apoptosis. By comparison, taking advantage of cloned TCRs derived from T cell clones reactive with male-specific molecules, using TCR transgenic mice it was possible to document positive selection of female thymocytes when the male-specific molecules were absent. Focusing on the molecular mechanisms of T cell ‘help’ for the generation of AFCs following the path opened by the elucidation of the IL-2 molecule, several groups were successful in the identification, isolation and characterization of three new interleukin molecules (IL-4, IL-5, and IL-6) that promote the proliferation and differentiation of B cells. In addition, the identification of a B cell surface molecule (CD40) that augmented BCR-stimulated proliferation and differentiation led to the discovery of a T cell activation surface molecule that proved to be the CD40-ligand, thus finally providing a molecular explanation for ‘linked or cognate’ recognition when T cells and B cells interact physically. Accordingly, the decade after the generation of the first T cell clones saw the elucidation of the molecular mechanisms